Implementasi Teori Belajar Behavioristik Pada Pembelajaran Matematika Kelas V SDN 13 Tilamuta - Amrain, Sri Delsya; Nasibu, Ana Anggriana; Abud, Farha; Annisa, Nur; Pou, Apriun; Uno, Winda Anggriyani (Journal of Education and Teaching Learning, 2023)
This study was conducted due to elementary school students' lack of understanding of mathematics. The aim is to assess the implementation of behavioristic learning theory in mathematics learning in class V. This study uses qualitative descriptive methods with observation, interviews, and documentation. The results showed that the implementation of behavioristic learning theory improved students' understanding in mathematics learning.